Experience Music Experiment: Pragmatism and Artistic Research - Brooks, William (Leuven Leuven University Press, 2021)
“Truth happens to an idea.” So wrote William James in 1907; and twenty-four years later John Dewey argued that artistic experience entailed a process of “doing and undergoing.” But what do these ideas have to do with music, or with research conducted in and through music—that is, with “artistic research”? In this collection of essays, fourteen very different authors respond with distinct and challenging perspectives. Some report on their own experiments and experiences; some offer probing analyses of noteworthy practices; some view historical continuities through the lens of pragmatism and artistic experiment. The resulting collection yields new insights into what musicians do, how they experiment, and what they experience—insights that arise not from doctrine, but from diverse voices seeking common ground in and through experimental discourse: artistic research in and of itself.
Contributors: William Brooks (Orpheus Institute), Richard Shusterman (Florida Atlantic University), Winnie Huang (Orpheus Institute/University of Antwerp/Royal Conservatoire Antwerp), Marco Fusi (Orpheus Institute/University of Antwerp/Royal Conservatoire Antwerp), Victoria Tzotzkova (Massachusetts Institute of Technology) and Fiona Smyth (Trinity College Dublin), Clare Lesser (New York University Abu Dhabi), Caitlin Rowley (Bath Spa University), Nicholas Brown (Trinity College Dublin), Ivana Miladinović Prica (University of Arts in Belgrade), Thibault Galland (Université Libre de Bruxelles), Garry L. Hagberg (Bard College), Ann Warde (Independent scholar), Deniz Ertan (Independent scholar) and Ambrose Field (University of York)
Keywords: Artistic research